Effect of Tryptophan Analogs on Derepression of the Escherichia coli Tryptophan Operon by Indole-3-Propionic Acid - Pauley, Robert J. (1978)
The abilities of 14 tryptophan analogs to repress the tryptophan (trp) operon have been studied in Escherichia coli cells derepressed by incubation with 0.25 mM indole-3-propionic acid (IPA). trp operon expression was monitored by measuring the specific activities of anthranilate synthase (EC 4.1.3.27) and the tryptophan synthase (EC 4.2.1.20) β subunit. Analogs characterized by modification or removal of the α-amino group or the α-carboxyl group did not repress the trp operon. The only analogs among this group that appeared to interact with the trp aporepressor were IPA, which derepressed the trp operon, and d-tryptophan. Analogs with modifications of the indole ring repressed the trp operon to various degrees. 7-Methyl-tryptophan inhibited anthranilate synthase activity and consequently derepressed the trp operon. Additionally, 7-methyltryptophan prevented IPA-mediated derepression but, unlike tryptophan, did so in a non-coordinate manner, with the later enzymes of the operon being relatively more repressed than the early enzymes. The effect of 7-methyltryptophan on IPA-mediated derepression was likely not due to the interaction of IPA with the allosteric site of anthranilate synthase, even though feedback-resistant mutants of anthranilate synthase were partially resistant to derepression by IPA. The effect of 7-methyltryptophan on derepression by IPA was probably due to the effect of the analog-aporepressor complex on trp operon expression.